2015
DOI: 10.1159/000368484
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin-2 Does Not Ameliorate Nephropathy in an Experimental Model of Type-1 Diabetes

Abstract: Background/Aims: In diabetic nephropathy (DN), the current angiotensin-II-blocking pharmacotherapy is frequently failing. For diabetic cardiomyopathy (DC), there is no specific remedy available. Relaxin-2 (Rlx) - an anti-fibrotic, anti-inflammatory, and vasoprotecting peptide - is a candidate drug for both. Methods: Low-dose (32 µg/kg/day) and high-dose (320 µg/kg/day) Rlx were tested against vehicle (n = 20 each) and non-diabetic controls (n = 14) for 12 weeks in a model of type-1 diabetes induced in endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Serelaxin treatment for the final two weeks of diabetes did not impact these metabolic parameters. Our findings are similar to a previous study which reported serelaxin had no effects on blood glucose levels in Type 1 diabetic mice31. However, in a mouse model of Type 2 diabetes, serelaxin reduced blood glucose levels3032.…”
Section: Discussionsupporting
confidence: 92%
“…Serelaxin treatment for the final two weeks of diabetes did not impact these metabolic parameters. Our findings are similar to a previous study which reported serelaxin had no effects on blood glucose levels in Type 1 diabetic mice31. However, in a mouse model of Type 2 diabetes, serelaxin reduced blood glucose levels3032.…”
Section: Discussionsupporting
confidence: 92%
“…However, rhRLX may not be universally renoprotective, as it did not prevent diabetic renal complications in mouse models of type I diabetes (Wong et al , ; Dschietzig et al , ), when TGF‐β1 was not elevated in either model. Importantly, in a phase II scleroderma trial (Khanna et al , ), cessation of rhRLX after 24 weeks of administration resulted in a significant decline in renal function, as estimated by creatinine clearance (Khanna et al , ).…”
Section: Anti‐fibrotic Actions Of Relaxin In the Kidneymentioning
confidence: 99%
“…These effects are only partially dose‐dependent, with robust effects seen at physiological concentrations (Mookerjee et al , ). Importantly, the anti‐fibrotic actions of rhRLX may well be contingent on TGF‐β1, which may explain the lack of efficacy in models without aberrant TGF‐β1 expression (Wong et al , ; Dschietzig et al , ).…”
Section: Anti‐fibrotic Actions Of Relaxin In the Kidneymentioning
confidence: 99%
“…Relaxin reduced unilateral uteretic obstruction-induced renal disease by antagonizing the effect of TGF-β, and that this effect was enhanced by coadministration of mesenchymal stem cells (Hewitson et al, 2010; Huuskes et al, 2015). On the other hand, relaxin was not effective in a diabetes-related renal disease model (Wong et al, 2013; Dschietzig et al, 2015). However, unlike the unilateral uteretic obstruction models, TGFβ was not increased in the diabetic model.…”
Section: Relaxinmentioning
confidence: 97%